Political Communication Strategy of the Partai Demokrasi Indonesia Perjuangan in Efforts to Maintain Party Domination in West Lampung Regency - Susanto, Andika Heri; Restu Rahmawati (JPP (Jurnal Politik Profetik), 2023)
The main objective of this research is to examine and analyse the political communication strategy of the Partai Demoktasi Indonesian Perjuangan (PDI-Perjuangan) in an effort to maintain its dominance in West Lampung Regency. This research uses qualitative methods and is explained using Anwar Arifin's political communication strategy theory. In an effort to maintain its party dominance in West Lampung Regency, PDI-Perjuangan took the following steps; First, maintaining its figures and strengthening party institutions. Second, creating programmes for the community and compiling political messages tailored to the community by making maximum use of the mass media. Third, building consensus not only with political parties but also non-political institutions such as religious institutions and traditional groups and being willing to open up to the community. These steps were taken as an effort to maintain party dominance in West Lampung Regency.